Analisis Penyelidikan Tanah Box Culvert STA. 4+550 dan STA. 8+575 dengan Sondir Manual Paket I.4 – Pembangunan Jalan Kawasan Industri Terpadu (KIT) Batang - Sita, Tisara; Suryan, Viktor; Chandra, Putu Wisnu Ardia (Universitas Batanghari Jambi, 2024)
The Government of the Republic of Indonesia is developing the Batang Integrated Industrial Estate (KIT), a national strategic project in the shape of an industrial park. A particularly vital industrial region, the Batang Integrated Industrial Estate (KIT) is situated in the northern economic corridor of Java and has access to the Trans Java Toll Road, the rail network, as well as nearby dry ports and port facilities. In order to connect the roads in the Batang Integrated Industrial Estate (KIT) with district roads and national roads or North Coast roads (Pantura), Package I.4-Road Construction of the Batang Integrated Industrial Estate was constructed. In order to ascertain the pertinent stratigraphic and physical characteristics of the soil on which the construction site was built, a soil investigation was conducted during construction. This process is used to assess whether the soil is stable enough to support the construction of a building. Data will be gathered in the form of soil resistance forces against the sondir or cone layers following an investigation or soil study. The sondir test can also be used to determine the required foundation depth, to precisely determine the original soil's bearing capacity, and to choose the appropriate type foundation to use. Location of Sta. 4+550 has a Box Culvert with sufficient embankment height so that it needs to be replaced as deep as -2.00 meters, while the location of the Box Culvert is at Sta. 8+575 embankment height is higher, it requires analysis of soil bearing capacity and settlement so that the replacement depth and use of mini pile foundation can be determined.